2017
DOI: 10.1590/s0100-204x2017001200008
|View full text |Cite
|
Sign up to set email alerts
|

WorldView-2 sensor for the detection of hematite and goethite in tropical soils

Abstract: -The objective of this work was to simulate the bands of the WorldView-2 sensor from laboratory specters, in order to study its potential to detect iron oxides, besides proposing a spectral index based on the depth of the spectral feature (RHGt Pf ). The iron index (IFe) and the hematite index (IHm), developed by Madeira Netto for bands of Landsat TM-5 sensor, were adjusted for WorldView-2 to test the potential of the new yellow band. The results showed that the yellow band degrades to 2% compared to the red o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The FRro-I presented stronger absorption features than FRro-II due to the smaller particle size in the first endmember, especially those related to kaolinite features. Baptista and Teobaldo [45] examined iron oxides in the region using spectroscopy, and they found hematite percentages ranging from 0 to 20%, gibbsite from 0.8 to 6.8% for tropical Rhodic Ferralsols. These results agree with [3], who state that iron oxide content varies by 15% in the study area.…”
Section: Soils Spectral Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The FRro-I presented stronger absorption features than FRro-II due to the smaller particle size in the first endmember, especially those related to kaolinite features. Baptista and Teobaldo [45] examined iron oxides in the region using spectroscopy, and they found hematite percentages ranging from 0 to 20%, gibbsite from 0.8 to 6.8% for tropical Rhodic Ferralsols. These results agree with [3], who state that iron oxide content varies by 15% in the study area.…”
Section: Soils Spectral Behaviormentioning
confidence: 99%
“…It was possible to observe iron oxide features at specific points on the curve, with a predominance of goethite over hematite, in addition to kaolinite absorption features (1.4 µm and 2.205 µm), hydroxyl groups (1.4 µm and 1.9 µm), and gibbsite (2.265 µm). Previous studies [10,17,20,45] revealed that the soil mineral composition, which has a low content of primary minerals and a high content of oxides, indicates a high degree of weathering processes influencing soil colors. Hydromorphic soils usually exhibit a lower albedo due to the higher OM and residual moisture in the soil solution [4].…”
Section: Soils Spectral Behaviormentioning
confidence: 99%
“…Accordingly, uncovered soils or soils with sparse vegetation are perceived by high brightness values (Gleriani, 2003;Healey et al, 2005;Vorovencii, 2007). The brightness index is able to discriminate the vegetation from minerals in the soil, such as quartz or carbonates, especially when they are dry (Bannari et al, 2016;Baptista and Teobaldo, 2017;Demattê et al, 2014). In the EPA of Uberaba River basin, Rodrigues et al (2019) reported a spatial correlation between brightness and soil loss, more evident in the dry season, using cross tabulation.…”
Section: Tablementioning
confidence: 99%